Author Correction: Microbial life and biogeochemical cycling on land 3, 220 million years ago. Issue 12 (December 2018) - Homann, Martin; Sansjofre, Pierre; Zuilen, Mark; Heubeck, Christoph; Gong, Jian; Killingsworth, Bryan; Foster, Ian; Airo, Alessandro; Kranendonk, Martin; Ader, Magali; Lalonde, Stefan
In the version of this Article originally published, author Magali Ader was wrongly linked to affiliation 3; it should have been affiliation 2. This error has now been corrected in the online versions.